Nest-Site Characteristics of Northern Bobwhites Translocated Into Weeping Lovegrass CRP - C. Wade Abbott; C. Brad Dabbert; Duane R. Lucia; Robert B. Mitchell; Alicia K. Andes (National Quail Symposium Proceedings, 2017)
Habitat loss and fragmentation have been considered major causes for the decline of northern bobwhite (Colinus virginianus). There are . 400,000 ha of weeping lovegrass (Eragrostis curvula) Conservation Reserve Program (CRP) fields in the Southern High Plains of Texas some of which could be modified to provide usable habitat for northern bobwhites. Timely colonization of improved CRP habitat by northern bobwhite is unlikely without transplantation, because of distance from existing populations. We radio-marked and transplanted 94 northern bobwhite into weeping lovegrass CRP and monitored nest success. We recorded high nest success in 2002 (70%) and 2003 (71%) for northern bobwhite nesting in weeping lovegrass CRP in the area studied. The composition of weeping lovegrass CRP fields available in our study area appears to be suitable nesting cover for northern bobwhite.
Keywords: artificial brush structures; Colinus virginianus; Conservation Reserve Program; nesting ecology; northern bobwhite; Southern High Plains; weeping lovegrass